Follow-Up in Head and Neck Cancer: A Management Dilemma. (14th January 2015) - De Felice, Francesca; Musio, Daniela; Tombolini, Vincenzo
Abstract : Follow-up program in squamous cell carcinoma of head and neck district is crucial to detect locoregional recurrence and second primary tumors and to manage treatment toxicities. The choice of the appropriate frequency of visits and imaging modality can be troublesome. Details of timing surveillance and type of diagnostic procedure are still not well defined. This review highlights the problem from a clinician's point of view.